The Role of Food Allergy in Atopic Dermatitis - Trogen, Brit; Verma, Megha; Sicherer, Scott H.; Cox, Amanda (Dermatologic clinics, 2024)
Atopic dermatitis (AD) and food allergies are 2 atopic conditions that tend to develop early in life. Their interrelationship has been a topic of controversy and many studies. The presence of atopic dermatitis in infancy and early childhood, particularly if severe, is a risk factor for the development of immunoglobulin E (IgE) -mediated food allergies. While it is common for children with AD to demonstrate extensive sensitization to foods, serum IgE testing is not always indicative of clinical allergy.